DISASTER IN SYARIAH PERSPECTIVE: A STUDY ON CUSTOM AND LOCAL WISDOM CORRELATION . - Mochammad Sahid, Mualimin; Fettane, Amar (Fakulti Syariah Dan Undang-Undang UNIVERSITI SAINS ISLAM MALAYSIA & Fakultas Hukum UNIVERSITAS MUHAMMADIYAH, MATARAM, 2019)
The sources of Syariah (Islamic law) are classified into two categories; primary and secondary sources. In fiqh (Islamic jurisprudence), the classification is important for it will determine from which the ahkam (rules) of Allah are discovered, in which the dalil (guide) or source of Syariah will give weight. The majority of scholars agreed that there are four primary sources for Syariah; Quran, Sunnah, Qiyas (analogy). The other category is the secondary sources in which the scholars differ in utilising them as a basis in deriving the ahkam. Some scholars considered them as a source, whilst others decline to utilise them in deriving the rulings of Fiqh. or adat (custom) is one of the Syariah secondary sources defined as the matter on which a community of people agree in the course of their daily life, or it is a common usage to refer to specific actions repeatedly performed by individuals and communities. Majority of mazahib (schools of fiqh) consider a legal principle in respect of matters about which there is no definitive actions. They consider as a dalil when there is no specific nas (text) or it is contrary to any other dalil. Meanwhile, local wisdom (local knowledge) can be defined as a policy or noble values contained in the richness of the local culture in the form of traditions, manners and life motto